2022
DOI: 10.1155/2022/8699322
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Automatic Identification System Information and PSO-LSTM Neural Network in CRI Prediction

Abstract: Considering that collision accidents happen sometimes, it is necessary to predict the collision risk to ensure navigation safety. With the information construction in maritime and the popularity of automatic identification system application, it is more convenient to obtain ship navigation dynamics. How to obtain ship encounter dynamic parameters through automatic identification system information, assess ship collision risk, find out dangerous target ships, and give early warning and guarantee for ship naviga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…To address the problem of low accuracy and high complexity in models for ship trajectory estimation and collision risk evaluation, Abebe et al [54] proposed a hybrid Autoregressive Integrated Moving Average-Long Short-Term Memory (ARIMA-LSTM) model based on AIS data. Zhou et al [55] proposed the introduction of a particle swarm optimization (PSO) algorithm to optimise the LSTM model and determine a better prediction of collision risk. The results showed that LSTM based on a particle swarm optimization (PSO-LSTM) model can handle complex problems with higher accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To address the problem of low accuracy and high complexity in models for ship trajectory estimation and collision risk evaluation, Abebe et al [54] proposed a hybrid Autoregressive Integrated Moving Average-Long Short-Term Memory (ARIMA-LSTM) model based on AIS data. Zhou et al [55] proposed the introduction of a particle swarm optimization (PSO) algorithm to optimise the LSTM model and determine a better prediction of collision risk. The results showed that LSTM based on a particle swarm optimization (PSO-LSTM) model can handle complex problems with higher accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%